Analisis Pengaruh Hak Upah Kerja Bagi Peningkatan Kinerja Karyawan Detik Sumsel - Dwi Putri Maharani; Nuraida; Ahmad Harun Yahya (Journal of Media and Communication | E-ISSN : 3063-9581, 2024)
The background of this research is the problem of the right to wages and the obligations of basic tasks and functions in each field, where wages are a worker's right to meet their living needs, both primary and secondary needs. Work has obligations to the employment company Detik Sumsel. So the author determined the title of this research regarding "Analysis of the Effect of Work Wage Rights on Improving Employee Performance at Detik Sumsel". The aim of the research is to determine the effect of wage rights on the performance of Detik Sumsel employees. This type of quantitative research uses data collection techniques through observation, questionnaires and documentation. With data analysis techniques through validity tests, reliability tests, normality tests, simple linear regression tests and hypotheses, using the SPSS Version 26.00 program. The research results show. It can be seen from the obtained hypothesis test values which prove that the results of the t test calculation show that hin is 13.017 while  is concluded to be 1.69726 because the value of hin> e???? can be stated that Wage Rights (X) influence Employee Performance (Y). By obtaining a significance value of 0.000 <0.05, it is declared significant. The result of the Fcount value is 5.929 with the Ftable value being 3.34 so that the Fcount > Ftable value (5.929 > 3.34) means H0 is rejected and H1 is accepted. So it can be concluded that Wage Rights have a very positive and significant influence on employee performance in Detik Sumsel with a percentage score of 74.7% which is categorized as achieving the highest score or having a strong relationship.